IMPLEMENTASI IOT DALAM MONITORING SUHU DAN GAS AMONIA PADA KANDANG AYAM BERBASIS WEBSITE DENGAN FRAMEWORK LARAVEL - M Mujiono; Adimas Ketut Nalendra; Dimas Hafidh Fauzi; Niswatul Karromah (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
To increase eggs production, the management of laying hens must be considered, one of the method is to apply the temperature and ammonia gas levels, with suitable for critria for laying hens. it is necessary to monitor the temperature and ammonia gas in the laying hen cage, this method can fulfilled by implementing monitoring with the Internet of Things (IOT) using Arduino and monitoring it with a website based on the Laravel framework and storing sensor results in the database, to send sensor results to website can uses ESP8266 with the HTTP protocol. The tests in this study were divided into three parts with connectivity, functionality, and blackbox tests. The connectivity test ESP8266 resulted is able to connect to the website with HTTP Proctocol. Sensor functionality test shows that the sensor can detect temperature and ammonia gas levels in the cage. The blackbox test shows that the website can store and display sensor readings